“Self-Knowledge and Varieties of Human Excellence in the French Moralists.” - Blank, Andreas (British Journal for the History of Philosophy)

Das ›Goldene Zeitalter‹ im modernen Spanien. Zur Wirkmächtigkeit und Problematik eines kulturellen und literarischen Kanons - Schreckenberg, Stefan (Literaturwissenschaftliches Jahrbuch)
Speaking of a ‚Golden Age‘ or a Siglo de Oro while referring to Spanish History, Culture and Literature transforms an ancient myth into a historiographical concept, which seems rather problematical, even contradictory and at the same time, seen in a wider European context, exceptional. Nevertheless, the Siglo de Oro is still being used as a key term in contemporary academic works ‒ inside and outside Spain ‒ on the Early Modern period, but also as a highly controversial idea in political and ideological debates, especially on behalf of what may or may not be Spanish identity. This article seeks to give a brief overview of the discussions that try to define the Siglo de oro-concept and present the literary canon as well as the ideological implications linked to it. Starting in the aftermath of the epoch itself, that means the 18th century, it focuses on the convergence of political and esthetical discussions that oppose the ‘Two Spains’ during the 20th century on behalf of how to choose and interpret their ‘classics’. Finally, it tries to give a (necessarily incomplete) view on the actual situation, where the Golden Age myth still interferes not only in literary, but also socio-political debates.

Student Essays expressing forms of historical thinking. Annotations regarding a quantitative and dually qualitative analysis of 1100 papers for the “Geschichtswettbewerb des Bundespräsidenten” - Meyer-Hamme, Johannes; Wosnitza, Christopher (Special Edition History Education Research Journal)

Historical myth: a definition from the perspective of history education research - Meyer-Hamme, Johannes; Hinz, Felix; Grindel, Susanne; Bernhard, Roland (Eckert. Dossiers)

Research Statement: Urban Platooning - Hardes, Tobias (International Conference on Networked Systems (NetSys 2019), PhD Forum)
CACC systems have been proven to increase road utilization, safety and decrease fuel consumption by driving with a small headway at freeway speed. Such platooning systems are usually focused on freeway scenarios and most of the current research is done for this use case. Especially in urban scenarios at traffic lights and intersections there is a lot of potential to increase the traffic efficiency and safety by applying platooning mechanisms. Most of the techniques used on freeways are not applicable for urban scenarios, as freeways are more or less a multi lane one-way road. In my PhD project I want to investigate platooning as an application for urban scenarios. For this I plan to examine platooning for signalized and non-signalized intersections in a first step, but also consider platoon formation strategies and driver models for human driven platoons. The end result should be a set of algorithms and strategies to make urban and rural traffic more efficient and safer by the use of platooning. Evaluation and analysis will mainly be done by using simulations, but not limited to that.

Using Full Duplex Relaying to Reduce Physical Layer Latency in Platooning - Amjad, Muhammad Sohaib; Hardes, Tobias; Schettler, Max; Sommer, Christoph; Dressler, Falko (11th IEEE Vehicular Networking Conference (VNC 2019))
Intelligent Transportation Systems (ITS) are changing the way cars will drive in the future – improving, at the same time, the safety and the efficiency of road traffic. Platooning is one of the considered applications, helping cars to drive with very short safety gaps to improve road traffic capacity and to reduce air drag. A fundamental building block for such cooperative driving solutions is reliable and fast wireless communication. Usually, information from the leader of the platoon needs to be broadcast to all members, resulting in large interference ranges, or being relayed from car to car, introducing additional delays. We introduce a Full Duplex Relaying (FDR) system for use in platooning to overcome these limitations. Concentrating on IEEE 802.11p, we implement the system to explore the feasibility and also to conduct a first performance evaluation. Our results clearly demonstrate the significant performance gain, which at the same time allows to further reduce communication overhead and, thus, to safely increase platoon sizes 802.11p, we implement the system to explore the feasibility and also to conduct a first performance evaluation. Our results clearlydemonstrate the significant performance gain, which at the same time allows to further reduce communication overhead and, thus, to safely increase platoon sizes.

Towards Heterogeneous Communication Strategies for Urban Platooning at Intersections - Hardes, Tobias; Sommer, Christoph (11th IEEE Vehicular Networking Conference (VNC 2019))
Platooning promises to solve worldwide traffic problems by using wireless communication for tight control of convoys of vehicles to reduce their inter-vehicle gaps. To date, however, most research on platooning has focused on freeway scenarios. In this paper, we provide a realistic exploration of platooning in urban environments: We consider traffic lights and buildings, realistic vehicle dynamics, platooning controllers, and network communication. We highlight the challenges that urban platooning faces because of the particularities of the Radio Frequency (RF) channel, specifically near the centers of intersections. We demonstrate that using Visible Light Communication (VLC) as an alternative can alleviate some problems, but causes others. Using extensive simulations, we show how a situation-aware combination of VLC and RF communication can be used as a solution: It reduces the overall amount of lost information by approx. 85% compared to traditional approaches.

Dynamic Platoon Formation at Urban Intersections - Hardes, Tobias; Sommer, Christoph (44th IEEE Conference on Local Computer Networks (LCN 2019), Poster Session)
Platooning has repeatedly been shown to have the potential to increase both the efficiency and the safety of future road traffic. Yet, while there is ample research that illustrates its potential in freeway scenarios, the biggest challenges of traffic efficiency and safety lie in urban environments, which pose unique challenges: They are characterized by the presence of tight speed limits, intersections, traffic lights, and buildings. Moreover, work that has targeted such scenarios has, so far, not considered platoon formation strategies - or only considered idealized vehicle dynamics, platooning controllers, or wireless network dynamics. We fill this gap by investigating dynamic platoon formation at urban intersections controlled by regular traffic lights. We propose a fuel-efficient strategy for platoon formation at such intersections and investigate its performance using realistic simulation models of (all of) vehicle dynamics, platooning controllers, and wireless networking. Our investigation reveals both challenges in wireless networking as well as the potential of the proposed strategy to simultaneously save both 15 % of fuel and 14 % of travel time.

Björn Czeschick: Das Land- und Stadtgericht Büren 1815-1849 - Ströhmer, Michael (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte, Germanistische Abteilung)

Kosten, Konjunkturen, Effizienz. Jurisdiktionsökonomie und Gerichtsvielfalt im Nordwesten des Alten Reiches - Ströhmer, Michael (Unter der Linde und vor dem Kaiser. Neue Perspektiven auf Gerichtsvielfalt und Gerichtslandschaften im Heiligen Römischen Reich)

Paderborner Wasserkünste als technische Denkmale des europäischen Kulturerbes ECHY 2018 - Ströhmer, Michael (Westfälische Zeitschrift)

Erziehungswissenschaft als Verunsicherungswissenschaft. Nicht nur eine Kritik des Mobilitätsimperativs - Haker, Christoph; Otterspeer, Lukas (Debatte. Beiträge zur Erwachsenenbildung)
Sebastian Zicks erziehungswissenschaftliche Kritik des Mobilitätsimperativs ist Ausgangspunkt unseres Beitrags. Wir greifen diese Kritik auf, indem wir sie in zweifacher Hinsicht ergänzen: Erstens um einen Fokus auf soziale Mobilität, welche sich in Mobilitätsnarrativen mit räumlicher Mobilität als verwoben zeigt. Zweitens um die Perspektive auf Mobilität als Rückkehr, die wir von einer Perspektive auf Mobilität als Fortbewegung abgrenzen. Die Rückwärtsbewegung ist für uns eng an (Selbst-)Reflexionen und transformatorische Bildungsprozesse gebunden, wie sie in Didier Eribons autosozioanalytischem Vorhaben einer Rückkehr zu erkennen sind. Unsere Ausführungen münden erstens in einer Kritik am Imperativ des Bildungsaufstiegs, in dem mehr Bildung scheinbar immer mit individuellen und kollektiven Fortschritten einhergeht. Zweitens wenden wir die von uns herausgearbeitete Kritik reflexiv auf die Erziehungswissenschaft. Sie ist dann eine Verunsicherungswissenschaft, für die die Rückkehr, und damit das Hinterfragen eigener Selbstverständlichkeiten, konstitutiv ist.
Keywords: Rehabilitation; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Kritische Systemtheorie und Kritische Theorie sozialer Systeme. Ein Plädoyer für eine fruchtbare Unterscheidung - Alvear, Rafael; Haker, Christoph (Leviathan)
Die Systemtheorie und die Kritische Theorie sind Schulen, die Theoretikerinnen seit langem ein Zuhause bieten. In der Zeit ihres Bestehens kam es immer wieder zu Treffpunkten und Theoriekollisionen dieser beiden Traditionen des Denkens der Gesellschaft. Durch die hier entwickelte Metareflexion wird es möglich, zu analysieren, wie diese Theorietraditionen verbunden werden. Da sich die aktuelle Diskussion auf die Perspektive der Systemtheorie beschränkt, ist es notwendig, die Verbindung auch aus der Perspektive Kritischer Theorie zu debattieren. Denn erst die Unterscheidung der heute immer mehr ins Gespräch kommenden Kritischen Systemtheorie von der kaum diskutierten Kritischen Theorie sozialer Systeme macht es möglich, die volle Produktivität der Theoriekollisionen zu erkennen. Wir konzipieren unsere Metareflexion damit als eine Intervention im Sinne einer soziologischen Selbstkritik. Sie richtet sich gegen die Gefahr des theoretischen Dogmatismus und plädiert für die Öffnung der Kontingenz des eigenen Denkens der Gesellschaft.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Empirische Bildungsforschung im Wirbel unmittelbarer Rezeption - Otterspeer, Lukas; Haker, Christoph (Zeitschrift für Pädagogik)

Neurechte Adaptionen erziehungswissenschaftlichen Wissens: Konsequenzen für eine digitalepolitische Bildung. - Haker, Christoph; Otterspeer, Lukas (Medien & Erziehung)

Das ›Goldene Zeitalter‹ im modernen Spanien. Zur Wirkmächtigkeit und Problematik eines kulturellen und literarischen Kanons - Schreckenberg, Stefan (Literaturwissenschaftliches Jahrbuch)

Numerically Investigating Residues of Weighted Zeta Functions on Schottky Surfaces - Schütte, Philipp

Resonances and Scattering Poles in Symmetric Spaces of Rank One - Hilgert, Joachim; Parthasarathy, A.; Hansen, S. (Inter. Math. Research Notices)

Naar het onbekende: perspectieven op literatuur, cultuur en kennis - van der Meer, Anne-Fleur; Schrover, Wouter; Moser, PH; Onrust, Margreet

On the Adoption of Standard Encoding Formats to Ensure Interoperability of Music Digital Archives: The IEEE 1599 Format - Andrea Ludovico, Luca; Baratè, Adriano; Simonetta, Federico; Mauro, Davide Andrea (6th International Conference on Digital Libraries for Musicology)